SCHeMA EU Project Summer School Report (Bilbao June 16 – 17, 2016) - Mahfuza Akter; Olaya Roman; Hu Ruoyu; Melina Abdou; Miquel Coll Crespi; Maria Cuartero Botia; Marianna Fighera; Teba Gil-Diaz; Justyna Lucja Kowal; Florian Luxenburger; Cristiana Mirasole; Nadezda Pankratova; et al. (CHIMIA, 2017)
This conference report describes the training activities that took place in the frame of the Integrated in Situ Chemical MApping probe (SCHeMA) summer school organized from the 14th to the 16th of June 2016 in Bilbao (Spain).